Music as a Tool for Ethics - María Gemma Sánchez González (Multidisciplinary Journal for Education, Social and Technological Sciences)
The current musical situation nowadays reflects a fast-technological change that has contributed to main social issues, such as a tangible crisis of values globally. The impact of music lyrics, nevertheless, could be a powerful useful tool to engage people in different ethical values leading to an improvement of relationships of any nature. Can music be that magic wand? This study aims at measuring the impact of lyrics on values of people and the power to improve norm activation. A questionnaire based on the Likert scale was conducted among 281 subjects either at university or with university studies. Results were analysed using the structural equation model SEM-PLS, which showed the relevance of items and connected hypotheses and a significant prediction capacity (R2= 0.458). Conclusions exposed that music can predict attitude change and become a tool for ethics.